1997
DOI: 10.3109/02656739709023558
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal whole body hyperthermia treatment of HIV patients, a feasibility study

Abstract: The literature supports that the retrovirus, Human Immunodeficiency Virus (HIV), which is thought to cause Acquired Immunodeficiency Syndrome (AIDS), is heat sensitive at temperatures which can be achieved in man. Invasive or non-invasive induction of whole body hyperthermia (WBH) has been used to treat an array of illnesses, primarily in the field of oncology, until recently. Non-invasive methods have proven to be less toxic than invasive means. However, new technology and refined patient management have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Nevertheless, serious complications as rhabdomyolysis and probably as a consequence hyperkaliemia, were troublesome, necessitating restraint extrapolation to human experiments. Studies using comparable WBH techniques in humans in, respectively, six HIV patients, five patients with non–small cell lung cancer, and six patients with metastatic sarcoma, reaching a body temperature of up to 42°C–42.5°C for 2 hr, did not encounter these features at the same magnitude (Locker et al, ; Zablow et al, ; Zwischenberger et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, serious complications as rhabdomyolysis and probably as a consequence hyperkaliemia, were troublesome, necessitating restraint extrapolation to human experiments. Studies using comparable WBH techniques in humans in, respectively, six HIV patients, five patients with non–small cell lung cancer, and six patients with metastatic sarcoma, reaching a body temperature of up to 42°C–42.5°C for 2 hr, did not encounter these features at the same magnitude (Locker et al, ; Zablow et al, ; Zwischenberger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although rhabdomyolysis is a known complication of heat stroke, in the literature of human eWBH, this complication is not described to the same extent as we found in our animal model (Yoshizawa et al, ). In humans receiving eWBH, Zwischenberger et al reported a CK rise up to 1846 ± 1823 U/L 2 hr after the procedure (normal value <170 U/L), Locker et al described grade 1 (National Cancer Institute Common Toxicity Criteria) CK rise in 33% and grade 2 in 25% of the patients (time interval of occurrence of CK rise not reported) and Zablow et al also reported mild CK level increases, spontaneously recovering after 2 weeks (only measured after 3 and 14 days) (Locker et al, ; Zablow et al, ; Zwischenberger et al, ). The discordance of the described CK elevations in the literature with our observations might be explained by a pig‐specific stress‐related syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Local, regional, and whole body are all methods in which hyperthermia may be administered. Extracorporeal is one type of whole body hyperthermia used in oncology, as well as infectious diseases (1,2). Currently, whole body hyperthermia is being used in a variety of cancers, HIV, and hepatitis C. A core body temperature of 41.8 °C has generally been accepted in the use of whole body hyperthermia in humans (3).…”
Section: Introductionmentioning
confidence: 99%